Detection of Immunological Response of Exotoxins Producing Pseudomonas aeruginosa - Soghi, Ahlam Ali; Alkhudhairy, Miaad K. (Medical Science Journal for Advance Research, 2025)
Abstract: Pseudomonas aeruginosa is responsible for increasing the mortality rate of burn patients, especially those strains that produce toxins. Therefore, this study aimed to evaluate the immune response to exotoxins produced by isolates that were collected from burn patients at the Burns Center in Najaf City of Iraq for the period from October 1st to December 1st, 2023. A total of 48/ 178 (27%) P. aeruginosa test isolates identified, 23 and 25 of which were female and male, respectively. The age groups of inpatients ranged from 5 to 55 years. Using molecular techniques, the polygenic pattern of exotoxin-encoding genes was predominant, especially the pattern (exoT+exoS+exoY) in 7 (58.4%) isolates, while no single gene was identified. Immunologically, the concentration of Interferon-Gamma (IFN-γ) was measured, and it was found higher in the inpatient group compared to the healthy control group. Moreover, it was found higher in the patient group (300.233 and 298.212) pg/ml in the 10- and 20-year age groups, respectively. While the level of IFN-γ in the inpatient group and the healthy control group was (310.123 and 52.222) pg/ml in females, which was higher than its concentration in males.